mTORC1 as a Regulator of Mitochondrial Functions and a Therapeutic Target in Cancer - de la Cruz López, Karen Griselda; Toledo Guzmán, Mariel Esperanza; Sánchez, Elizabeth Ortiz; García Carrancá, Alejandro (Frontiers in Oncology, 2019)
Abstract Continuous proliferation of tumor cells require many adjustments of energy metabolism to rapidly fuel cell growth and division. This energetic reprogramming often comprises deregulated glucose uptake and lactate production in the presence of oxygen, a process known as the “Warburg effect”. For many years it was thought that the Warburg effect was the result of mitochondrial damage however, unlike this proposal, tumor cell mitochondria not only retain their functionality, but also instrumental for integrating a variety of signals and adjusting the metabolic activity of the tumor cell. The mammalian/mechanistic target of rapamycin complex 1 (mTORC1) is a master regulator of numerous cellular processes implicated in proliferation and cell growth. mTORC1 controls cellular metabolism mainly by regulating the translation and transcription of metabolic genes. Here we present an overview on the role of mTORC1 in the regulation of mitochondrial functions in cancer, considering new evidences showing that mTORC1 regulates the translation of nucleus-encoded mitochondrial mRNAs that result in an increased ATP mitochondrial production. Moreover, we discuss the relationship between mTORC1 and glutaminolysis, as well as mitochondrial metabolites. In addition, mitochondrial fission processes regulated by mTORC1 and its impact on cancer are discussed. We finally also review the therapeutic efficacy of mTORC1 inhibitors in cancer treatments, considering its use in combination with other drugs, in particular inhibitors of cellular metabolism, that could help improve their anti neoplastic effect and eliminate cancer cells in patients.